Features Of Creative Thinking Of Primary Grade Students - Muhammadjonova, Zarnigor (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the features of creative thinking of primary school students, the factors of their psychological and pedagogical development, as well as the content of the process of forming creative thinking. The study systematically studied internal (motivational, emotional, intellectual) and external (teacher's activities, educational environment, methodological approaches) factors affecting the thinking activity of students. It also highlights the role of interactive methods, the use of problem situations, innovative educational technologies, and an integrative approach in the development of creative thinking.